The migration of elites in a borderless world: citizenship as an incentive for professionals and managers? - Pohlmann, Markus (Citizenship and migration in the era of globalization, 2012)
This chapter examines whether migration patterns of professionals and managers sustain the assumption that these are transnational citizens. Instead of a braindrain/braingain pattern between countries, empirical findings based on data from the U.S., East Asia and Germany highlight the fact that the internationalization of management is rather a matter of “brain circulation”. These findings are discussed against the backdrop of mainstream globalization theories that regard citizenship as an incentive for transnationals, yet empirical inquiry reveals that actual migration patterns require a sociological explanation based on cultural differences in career systems.
Gesehen am 23.11.2017